Finite non-abelian 2-groups such that any two distinct minimal non-abelian subgroups have cyclic intersection - Janko, Zvonimir (Journal of group theory, 2010)
We determine here the groups of the title up to isomorphism. As a result we obtain three infinite classes of 2-groups and an exceptional group of order 2 5 .
Gesehen am 14.07.2023